The constitutional right to health in Hungary - Julesz, Máté (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
In Hungary, the right to health is implied in the Fundamental Law of 2011. The legal history of the constitutional right to health in Hungary dates back to 1949, although this was preceded by an earlier assumption of social human rights. The Hungarian constitutional right to health implies the most important notional elements of the human right to health. One can see that the communist type of constitutional right to health largely differs from the right to health under a democratic rule of law. The Hungarian Constitution of 1949 and the Constitution of the Democratic People’s Republic of Korea currently in force reflect a 19th-century social human rights conception. In present-day Hungary, there is no room for a similar understanding. Hungary’s present constitutional health law is shaped according to the needs of a society within a free market economy.